Nerve–macrophage interactions in cardiovascular disease. (26th June 2021) - Fujiu, Katsuhito; Manabe, Ichiro
Abstract: The heart is highly innervated by autonomic neurons, and dynamic autonomic regulation of the heart and blood vessels is essential for animals to carry out the normal activities of life. Cardiovascular diseases, including heart failure and myocardial infarction, are characterized in part by an imbalance in autonomic nervous system activation, with excess sympathetic and diminished parasympathetic activation. Notably, however, this is often accompanied by chronic inflammation within the cardiovascular tissues, which suggests there are interactions between autonomic dysregulation and inflammation. Recent studies have been unraveling the mechanistic links between autonomic nerves and immune cells within the cardiovascular system. The autonomic nervous system and immune system also act in concert to coordinate the actions of multiple organs that not only maintain homeostasis but also likely play key roles in disease–disease interactions, such as cardiorenal syndrome and multimorbidity. In this review, we summarize the physiological and pathological interactions between autonomic nerves and macrophages in the context of cardiovascular disease. Abstract : Neuroimmune interactions in cardiology